Literature Review : Efektivitas Antimikroba Kulit Manggis (Garcinia Mangostana L.) terhadap Cutibacterium Acnes dan Staphylococcus Epidermidis - Waode Afiqah Muyyasarah Nur Bahrani; Dian Amelia Abdi; Zulfiyah Surdam; Yani Sodiqah; Lisa Yuniati (KOLONI, 2026)
Acne vulgaris is a common skin disease frequently associated with the colonization of Cutibacterium acnes and Staphylococcus epidermidis bacteria; however, repeated use of antibiotics risks triggering resistance, necessitating effective and safe natural alternatives. This study presents a literature review with a narrative review design on the potential of mangosteen peel (Garcinia mangostana L.) as an anti-acne antibacterial agent by analyzing 10 articles from PubMed, NCBI, and Google Scholar (2017–2025) that met the inclusion criteria. The results demonstrated that mangosteen peel extract possesses antibacterial activity against C. acnes and S. epidermidis, as evidenced by the formation of inhibition zones along with supportive Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values. The key compound $α$-mangostin from the xanthone group plays a dominant role through the disruption of bacterial cell membranes and the inhibition of microbial metabolism, with flavonoids and tannins contributing synergistically. Furthermore, the antibacterial effectiveness is influenced by the extraction method, solvent type, and extract concentration, with a tendency for nonpolar–semipolar solvents to yield higher activity. Overall, these findings confirm the potential of mangosteen peel as a natural candidate for acne vulgaris therapy, although extract standardization, determination of optimal dosage, toxicity testing, and controlled clinical trials are still required to ensure safety, efficacy, and reproducibility in clinical applications.